DIGITAL TECHNOLOGY ADOPTION TO SUPPORT SUSTAINABLE INNOVATION AMONG MSMEs IN INDONESIA - Khabib Alia Akhmad; Singgih Purnomo; Suci Purwandari; Ilham Sentosa (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Digital transformation has become a critical necessity for micro, small, and medium enterprises (MSMEs) to enhance competitiveness and foster sustainable innovation. This study aims to analyze some factors influencing the adoption of digital technologies by MSMEs and to examine their impact on sustainable innovation capabilities. Data were collected from 329 MSMEs in the manufacturing sector in Indonesia through a quantitative survey. The analysis employed a bivariate logistic regression model to investigate the relationship between firm characteristics (size, age, sector) and the utilization of digital technologies to support innovation. The findings indicate that firm size and growth orientation have a significant influence on the adoption of digital technologies and the pursuit of sustainable innovation. This study underscores the importance of technological support for larger MSMEs in facilitating innovative processes and ensuring business sustainability. Theoretically, this study contributes to the literature on technology adoption in the context of MSMEs in the developing countries. Practically, the findings offer valuable implications for policymakers and industry stakeholders in designing more targeted digitalization interventions to strengthen the innovation capacity of the MSME sector.